Construction of ternary hybrid layered reduced graphene oxide supported g-C3N4-TiO2 nanocomposite and its photocatalytic hydrogen production activity. (22nd February 2018) - Hafeez, Hafeez Yusuf; Lakhera, Sandeep Kumar; Bellamkonda, Sankeerthana; Rao, G. Ranga; Shankar, M.V.; Bahnemann, D.W.; Neppolian, Bernaurdshaw
Abstract: Reduced graphene oxide (rGO) supported g-C3 N4 -TiO2 ternary hybrid layered photocatalyst was prepared via ultrasound assisted simple wet impregnation method with different mass ratios of g-C3 N4 to TiO2 . The synthesized composite was investigated by various characterization techniques, such as XRD, FTIR, Raman Spectra, FE-SEM, HR-TEM, UV vis DRS Spectra, XPS Spectra and PL Spectra. The optical band gap of g-C3 N4 -TiO2 /rGO nanocomposite was found to be red shifted to 2.56 eV from 2.70 eV for bare g-C3 N4 . It was found that g-C3 N4 and TiO2 in a mass ratio of 70:30 in the g-C3 N4 -TiO2 /rGO nanocomposite, exhibits the highest hydrogen production activity of 23, 143 μmol g −1 h −1 through photocatalytic water splitting. The observed hydrogen production rate from glycerol-water mixture using g-C3 N4 -TiO2 /rGO was found to be 78 and 2.5 times higher than g-C3 N4 (296 μmol g −1  h −1 ) and TiO2 (11, 954 μmol g −1  h −1 ), respectively. A direct contact between TiO2 and rGO in the g-C3 N4 -TiO2 /rGO nanocomposite produces an additional 10, 500 μmol g −1 h −1 of hydrogen in 4 h of photocatalytic reaction than the direct contact between g-C3 N4 and rGO. The enhanced photocatalytic hydrogen production activity of the resultant nanocomposite can be ascribed to the increased visible light absorption and an effective separation of photogenerated electron-hole pairs at the interface of g-C3 N4 -TiO2 /rGO nanocomposite. The effective separation and transportation of photogenerated charge carriers in the presence of rGO sheet was further confirmed by a significant quenching of photoluminescence intensity of the g-C3 N4 -TiO2 /rGO nanocomposite. The photocatalytic hydrogen production rate reported in this work is significantly higher than the previously reported work on g-C3 N4 and TiO2 based photocatalysts. Highlights: g-C3 N4 -TiO2 /rGO (CTR) was prepared via ultrasound assisted wet impregnation method. Anatase-brookite phase of TiO2 shows significantly higher H2 production activity. CTR produces an additional 10, 500 μmolg −1 of H2 in 4 h compare to TiO2 -g-C3 N4 /rGO. The charge carrier separation is more effective at TiO2 /rGO interface compare to g-C3 N4 /rGO.